Return to the Kingdom of Childhood : Re-envisioning the Legacy and Philosophical Relevance of Negritude - Thiam, Cheikh (Book collections on Project MUSE., 2014)
"Return to the Kingdom of Childhood: Re-envisioning the Legacy and Philosophical Relevance of Negritude examines the philosophy of Negritude through an innovative analysis of Leopold Sedar Senghor's oeuvre. In the first book-length study of Senghorian philosophy, Cheikh Thiam argues that Senghor's work expresses an Afri-centered conception of the human while simultaneously offering a critique of the Western universalization of "man." Senghor's corrective, descriptive, and prescriptive theory of humanness is developed through a conception of race as a cultural manifestation of being. Thiam contends that Senghor's conception of race entails an innovative Afri-centered epistemology and ontology. For Senghor, races are the effects of particular groups' relations to the world. The so-called "Negroes," for example, are determined by their epistemology based on their fluid understanding of the ontological manifestations of being. The examination of this ontology and its ensuing epistemology, which is constitutive of the foundation of Senghor's entire oeuvre, indicates that Negritude is a postcolonial philosophy that stands on its own"--From back cover.